Effect of high hydrostatic pressure (HHP) on proteins, lipids, and water state of three different thawed seafood products - de Aguiar Saldanha Pinheiro, Ana Cristina; Tappi, Silvia; Soglia, Francesca; Baldi, Giulia; Molina Hernandez, Junior Bernardo; Laghi, Luca; Dalla Rosa, Marco; Petracci, Massimiliano; Rocculi, Pietro (Italian Journal of Food Science, 2025)
The aim of this research is to investigate the changes in the state of different components of seafood muscle subjected to High Hydrostatic Pressure (HHP), namely water, proteins, and lipids. Three seafood products were subjected to three pressure levels (400, 500, and 600 MPa) for 10 min and analyzed through a multi-analytical approach, including differential scanning calorimetry and protein solubility assay, time-domain nuclear magnetic resonance (TD-NMR), and various lipid oxidation and hydrolysis assays. Results showed a similar level of variation for some parameters, such as whitening and water mobility, across all species and pressure levels investigated, while protein denaturation, protein solubility, and texture were more effective in discriminating the samples—particularly for grey mullet, which appeared to be the most affected and, therefore, the least suitable for HHP treatment. Only a slight increase was observed in lipid oxidation parameters. In conclusion, the results highlight the importance of selecting raw material based on its response to pressure application.